Hepatitis C virus infection and global kidney health: the consensus proceedings of the International Federation of Kidney Foundations - Saadi, Gamal; Kalantar-Zadeh, Kamyar; Almasio, Piero; Ashuntantang, Gloria; Barsoum, Rashad; Bruchfeld, Annette; Doss, Wahid; El-Fishawy, Hussein; El Raziky, Maissa; El-Serafy, Magdy; et al. (African Journal of Nephrology, 2020)
Hepatitis C virus (HCV) infection is an important cause of major morbidities including chronic liver disease, liver cancer, acute kidney injury and chronic kidney disease (CKD). Among patients with kidney disease who have HCV infection, the clinical outcomes are worse. The prevalence of HCV infection is exceptionally high among dialysis and kidney transplant patients throughout the globe. It is estimated that 5% to 25% or more of dialysis-dependent patients are affected. Almost half of all deaths in CKD patients, including HCV-infected patients, are due to cardiovascular disease, and HCV-infected patients have higher mortality. Given the importance and impact of the HCV epidemic on global kidney health, and the status of Egypt as the nation with the highest prevalence of HCV infection in the world along with its initiatives to eradicate HCV, the International Federation of Kidney Foundations convened a consensus conference in Cairo in December 2017. This article reflects the opinions and recommendations of the contributing experts and reiterates that, with the current availability of highly effective and well tolerated pharmacotherapy, CKD patients should be given priority for the treatment of HCV, as an important step towards the World Health Organization’s goal of eliminating viral hepatitis as a public health problem by 2030.